Development of Electric Power Transmission Using Laser with Fiber Optics for Disaster Equipment in Remote Areas - Mariana Elisabet Purba mariana; Bambang Widiyatmoko; Kerista Tarigan (Talenta Publisher, 2023)
Instrumentation for monitoring natural disasters as an integrated early warning system has been widely developed and placed in areas that are estimated to be prone to natural disasters to help the government and the community. The purpose of this study is to take pre- and post-disaster measures to reduce losses experienced. However, the placement of these monitoring instruments has many shortcomings, one of which is the theft of the main components of the power supply and the battery used to activate the instrument. An alternative technology to solve this problem is to rely on power transmission with fiber optic-based light. The laser will be sent to the location using fiber optics which is then emitted to the solar panels so that the laser is converted into electrical energy. The power produced by an 810 nm laser-illuminated solar panel with a power of 140 mW is 7.76 mW. The power to produce an 810 nm laser must provide the same power as a monochromatic solar panel, which is illuminated by the sun's intensity at 25.395 mW.